2001
DOI: 10.1086/322468
|View full text |Cite
|
Sign up to set email alerts
|

Electrodynamic Structure of an Outer Gap Accelerator: Location of the Gap and the Gamma‐Ray Emission from the Crab Pulsar

Abstract: We investigate a stationary pair-production cascade in the outer magnetosphere of a spinning neutron star. The charge depletion due to global Ñows of charged particles causes a large electric Ðeld along the magnetic Ðeld lines. Migratory electrons and/or positrons are accelerated by this Ðeld to radiate curvature gamma rays, some of which collide with the X-rays to materialize as pairs in the gap. The replenished charges partially screen the electric Ðeld, which is self-consistently solved together with the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
(31 reference statements)
2
38
0
Order By: Relevance
“…CHRI have shown that the inner boundary of the static outer gap begins at the null charge surface (6 = B ¼ 0). Recently, Hirotani & Shibata (2001) have shown that if there is injected current from the inner boundary, the position of the inner boundary can shift either toward the star or even closer to the light cylinder depending on the sign and the magnitude of the injected current. However, it is not clear what causes this injected current.…”
Section: Outer Gap Modelsmentioning
confidence: 99%
“…CHRI have shown that the inner boundary of the static outer gap begins at the null charge surface (6 = B ¼ 0). Recently, Hirotani & Shibata (2001) have shown that if there is injected current from the inner boundary, the position of the inner boundary can shift either toward the star or even closer to the light cylinder depending on the sign and the magnitude of the injected current. However, it is not clear what causes this injected current.…”
Section: Outer Gap Modelsmentioning
confidence: 99%
“…It is generally believed that the charge density in the pulsar magnetosphere is high enough to screen the electric field E || parallel to the magnetic field, thus the corotation condition E · B = 0 is maintained everywhere except for a few locations. The regions where E || = 0 can exist quite close to the surface of the neutron star -in the polar caps (polar cap/inner gaps model), or at a distance comparable to the light cylinder along the null charge surface defined by the condition Ω · B = 0, where the corotation charge density changes sign (outer gap model) (see, however, Hirotani & Shibata 2001). …”
Section: Magnetospheric Multi-gev Radiation From Velamentioning
confidence: 99%
“…Certainly it is very necessary to improve gap models of BSSs, especially for the interaction between inner and outer vacuum gaps; a dynamically consistent model with both kinds of gaps may be essential to understand the observations. It is worth noting that the null surface is not necessary to serve as the inner boundary of the outer gap; it may be possible that the inner boundary of the P-N junction (Holloway 1973) could be much lower (Hirotani & Shibata 2001). …”
Section: Magnetospheric and Thermal Emissionmentioning
confidence: 99%